Fostering Reflective Learning among Reticent and Reluctant Students in Clinical Dental Training in the Indian Scenario - PS, Manoharan; KR, Sethuraman; BV, Adkoli; R, Saravanakumar (International Journal of Psychosocial Rehabilitation, 2020)
Clinical Dental Training should be aimed to induct reasoning power, reflective practice and decision making skills. Conventional approach of drill mode of performing cases repetitively would not suffice. Reflective practice is known to produce the aforementioned results. However in an Indian Scenario, majority of the students do not express themselves, volunteer to initiate any discussion or express their thoughts and learning in words in a practical scenario. These are the common obstacles noticed by the author in his earlier study on competency driven curriculum for dental interns. Based on the literature search and analyzing various reflective learning strategies, the first author has developed a collective reflective learning strategy model [CRLS] for clinical dental training. The present article outlines the model and the results of the initial implementation phase.